Enhanced resistance in Bi(Fe1-xScx)O3-0.3BaTiO3 lead-free piezoelectric ceramics: Facile analysis and reduction of oxygen vacancy. Issue 14 (November 2019) - Xun, Bo-Wei; Tang, Yu-Cheng; Chen, Jian-Yin; Zhang, Bo-Ping
Abstract: We reported a facile analysis and reduction of oxygen vacancy ( V O ) in 0.7Bi(Fe1- x Sc x )O3 -0.3BaTiO3 (0≤ x ≤0.08) ceramics. The leakage current mechanism was investigated intensively. Our results indicated that oxygen vacancies are the main cause for the high conductivity in BF-BT ceramics, and their concentration was quantitatively estimated from the Bi 3+ content and the average oxidation state of iron. The V O concentration was effectively suppressed and the insulation resistance was enhanced by almost two orders of magnitude after doping 2%mol Sc 3+ . The enhanced insulation resistance contributed to excellent piezoelectric properties with d 33 = 165 pC/N, T C = 505 °C, and k p = 26%. The proposed analysis method used to quantify the V O concentration provides valuable indications to reduce the leakage current density and improve the piezoelectric properties of BF-BT based ceramic.